Integrative approaches across green energy technologies: the role of innovations in human capital - Wadim Strielkowski; Evgeny Kuzmin; Maksim Vlasov (Academia Green Energy)
This article investigates the pivotal role of innovations in human capital in propelling sustainable socioeconomic development and transition to green energy technologies within the energy sector. Recognized as the linchpin of modern economies, the energy industry provides essential resources critical for industrial processes, transportation, and the overall functioning of society. Amid the global transition toward sustainable practices, the importance of not only advancing technological innovation but also enhancing human capital in this sector is increasingly acknowledged, especially in the light of the shift toward green and renewable energy alternatives. Employing a bibliometric approach, this study analyzes a collection of 1933 documents, encompassing research articles, conference papers, and book chapters, indexed in the Web of Science (WoS) database. Through a network cluster analysis of the textual and bibliometric data using the VOSviewer software, our findings suggest that investments in human capital are deemed crucial for fostering long-term sustainable economic growth within energy companies globally. Furthermore, the significance of human capital in the energy sector is observed to be escalating in prominence among researchers and academics, both within Russia and internationally. This growing interest underscores the vital role that skilled, knowledgeable, and innovative human resources play in navigating and driving the energy sector toward a more sustainable and renewable future.